Secondary School Students’ Attitude towards Mathematics - Thapa, Dhana Kumari; Paudel, Tara (Mathematics Education Forum Chitwan, 2020)
The major objective of this article is to describe the perception of self-efficacy and attitude towards mathematics of students studying science and mathematics in grade 12 in Kathmandu valley. Cross-sectional descriptive design and quantitative method were used to collect and analyze data. Data were collected from 318 randomly selected students studying science in grade 12, from nine different schools of Kathmandu valley through self-administered questionnaire. The survey showed that majority of girls and boys were encouraged by their parents to get enrolled in the science stream. Most of them chose mathematics courses to enter into the fields of engineering and technical sciences. From the observation we found that perceived self-efficacy is good i.e. both girls and boys have positive and good attitude towards mathematics courses. There is no gender variation in attitude of students learning mathematics between girls and boys. Therefore, attitude towards mathematics are less likely to be influenced by gender of students, castes and educational status of parents. Many students can be attracted towards mathematics field of study by providing information and counseling about academic opportunity for mathematics in higher education.